Cyber physical Autonomous Vehicular System CAVS A MAC layer perspective - Jahan, Ali; Md Arafatur, Rahman; Md Zakirul, Alam Bhuiyan; A. Taufiq, Asyhari; Mohammad Nomani, Kabir (Springer International Publishing, 2020)
Cyber-physical autonomous vehicular system (CAVS) plays an important role in the automotive industries to enable interactions among functioning elements, including sensors and actuators, in order to ensure seamless data exchange and communications. Internet of things (IoT) is one of the key enabling technologies for designing such a system. In this chapter IoT is incorporated on the vehicular system to address the challenges and issues on designing an efficient CAVS. Although incorporating IoT on CAVS requires full consideration of all the protocol stacks, this article is aimed to focus only on the analysis from a media access control (MAC) layer point of view. More specifically, this article highlights the impact of IoT on vehicular systems based on the statistical information, state-of-the-art on MAC perspective, the framework of CAVS, and the open research issues. The outcome of this work will assist significantly in designing an efficient CAVS.